Convenient Synthesis of 3-(2-Pyridyl)- and 8-(2-Pyridyl) Carbostyrils - SUDHIR KUMAR, P.; PANDA, JAGADEESH; RAVI KUMAR, B.V.V. (Asian Journal of Chemistry, 2010)
3-(ω-Bromoacetyl) carbostyril (1) and 4-methyl-7-methoxy-8-(robromoacetyl) carbostyril (5) on reaction with pyridine in refluxing toluene provide the pyridinium salts 2 and 6 respectively. Condensation of salts 2 and 6 with chalcones in acetic acid in the presence of ammonium acetate gives 3-(2-pyridyl) and 8-(2-pyridyl) carbostyrils in high yield.